Combustion Mode Design with High Efficiency and Low Emissions Controlled by Mixtures Stratification and Fuel Reactivity - Wang, Hu; Zheng, Zunqing; Liu, Haifeng; Yao, Mingfa (Frontiers in Mechanical Engineering, 2015)
This paper presents a review on the combustion mode design with high efficiency and low emissions controlled by fuel reactivity and mixture stratification that have been conducted in the authors’ group, including the charge reactivity controlled homogeneous charge compression ignition (HCCI) combustion, stratification controlled premixed charge compression ignition (PCCI) combustion, and dual-fuel combustion concepts controlled by both fuel reactivity and mixture stratification. The review starts with the charge reactivity controlled HCCI combustion, and the works on HCCI fuelled with both high cetane number fuels, such as DME and n-heptane, and high octane number fuels, such as methanol, natural gas, gasoline and mixtures of gasoline/alcohols, are reviewed and discussed. Since single fuel cannot meet the reactivity requirements under different loads to control the combustion process, the studies related to concentration stratification and dual-fuel charge reactivity controlled HCCI combustion are then presented, which have been shown to have the potential to achieve effective combustion control. The efforts of using both mixture and thermal stratifications to achieve the auto-ignition and combustion control are also discussed. Thereafter, both charge reactivity and mixture stratification are then applied to control the combustion process. The potential and capability of thermal-atmosphere controlled compound combustion mode and dual-fuel reactivity controlled compression ignition (RCCI)/highly premixed charge combustion (HPCC) mode to achieve clean and high efficiency combustion are then presented and discussed. Based on these results and discussions, combustion mode design with high efficiency and low emissions controlled by fuel reactivity and mixtures stratification in the whole operating range is proposed.